Political campaign spending limits - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2010)
Political campaign spending ceilings are purported to limit the incumbent's ability to exploit his fundraising advantage. If the challenger does not have superior campaign effectiveness, in contrast to conventional wisdom, we show that the incumbent always benefits from a limit as long as he has an initial voter disposition advantage, however small and regardless of the candidates' relative fundraising ability. If the challenger has higher campaign spending effectiveness, the effect of limits may be non-monotonic. If the incumbent enjoys a mild initial voter disposition advantage, a moderate limit benefits the challenger. Further restricting the limit favours the incumbent. Stricter limits may lead to the unintended consequence of increased expected spending.
hdl:10197/2668
Keywords: 330; Campaign finance legislation; Spending cap; Expenditure limit; Incumbency advantage; Efficiency in fundraising; Effectiveness of campaign spending; Initial voter disposition; All pay auction